The end of the timber frontier in northern Sweden - Cosatti, Alice (2022)
The Fennoscandian forests experienced drastic changes in the 19th century. The high demand for timber during the European industrialization pushed the timber companies towards increasingly remote forest landscapes for resource extraction. This study explores the concept of the so-called timber frontier which seeks to demarcate waves of forest use change, on priorly natural forest land, often inhabited by indigenous populations. The research scope of this study is confined to northernmost Sweden and aims to elucidate the dynamics defining its specific development and pinpoint where the timber frontier ended in this region. The timber frontier reached the uppermost Piteälven watershed area during the end of the 19th century. Historical logging traces of high-grading were searched for during a field survey in Tjeggelvas nature reserve. Independently collected archival data support the findings of the field survey. By analyzing a gradient from the lakeshore to the inner parts of the forest, the end of the timber frontier could be marked out. The results show clearly that logging occurred close to the river and along the lakeshore. The long-term ecological impact, however, remains blurred due to the low impact of historical high-grading extraction practices and the long time period that has passed since then. The historical records indicate that high costs for timber floating and low stand productivity were limiting further exploitation. Furthermore, the timber frontiers’ late arrival and the establishment of the first nature reserves in Sweden overlapped and might be reasons why the timber frontier came to an end in the researched area. Even after one frontier has come to a halt, there is a general tendency for new frontiers of resource extraction to arrive repeatedly on the same lands. Therefore, I suggest that a stronger protection is needed for this unique forest, and that the Sami land use rights are reinforced in order to protect Tjeggelvas nature reserve for future generations.